And who will make the chapatis? : a study of all-women panchayats in Maharashtra - Datta, Bishakha (Stree : Distributed by Bhatkal Books International, 1998)
All-women panchayats, which are elected institutions of local government, represent attempts by rural women to carve out a political space that will enable them to place their needs and priorities on the political agenda. Stories show how in some women are used as puppets by stronger (patriarchal) interests; but in the majority women take their own decisions and implement them, often outwitting the establishment. The authors used interview-based research methods, and preserved as far as possible the immediacy of oral communication in their work, as the title, a comment by a man when he heard that a woman wanted to attend a training camp.